A study on the protective effects of certan natural products against the possible brain damage induced by gamma radiation and/or metal toxicity in male rats - Ghada Mahmoud Ahmed Shafey; Amina Salem Attia; Hala Fahmy Zaki; Mona Abdellatif Elghazaly (Cairo : Ghada Mahmoud Ahmed Shafey, 2014)
Exposure to lead and/ or y-irradiation causes numerous malfunctions particularly in the brain. The present study was performed to investigate the possible role of grape seed extract (GSE;) 100 mg/kg/day; p.o) and ginkgo biloba extract (50 and 100 mg/kg; p.o.) in ameliorating the biochemical changes in brain of rats induced by i.p. administration of lead (25 mg/kg) daily for seven successive days in rats exposed to 6 Gy whole body y-radiation on day seven
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacology and Toxicology
Issued also as CD
Keywords: Ginkgo biloba extract; Grape seed extract; Lead